Blood metabolites during basketball competitions - Abdelkrim, N. B.; Castagna, C.; Fazaa, S. E.; Tabka, Z.; Ati, J. E. (The Journal of Strength and Conditioning Research, 2009)
This study examined basketball game blood hormonal and metabolite responses in 38 (8 guards, 18 forwards, and 12 centers) male national elite-junior players (age, 18.2 ± 0.5 years; height, 1.89 ± 0.1 m; body mass, 80.3 ± 6.7 kg; body fat, 8.2 ± 5.6%; maximum oxygen uptake V?o2max], 52.8 ± 2.4 ml/kg/min). At the moment of the investigation, players had 8 ± 1.6 years of competitive experience. Blood samples were collected at the beginning, at halftime, and at fulltime of 6 junior competitive games (Tunisian under 19 basketball championship). Game intensity was assessed monitoring heart rates (HR). During the game, players attained 93 ± 2% of maximal HR. Triglycerides (TG) and free fatty acids (FFA) concentrations significantly increased during the game, most markedly so in the second half. Postgame TG and FFA concentrations were significantly (p < 0.05 and p < 0.001, respectively) lower for guards (1.48 ± 0.22 and 0.88 ± 0.14 mmol/L, respectively) than for centers (1.88 ± 0.30 and 1.08 ± 0.09 mmol/L, respectively). Plasma glucose significantly increased at halftime (from 4.05 ± 1.27 to 5.98 ± 0.88 mmol/L; p < 0.001) but decreased in the second half. Serum insulin (INS) progressively decreased for all players during the game, whereas serum cortisol increased at the end of the first half (from 333 ± 129 to 487 ± 209 nmol/L; p < 0.001) to remain increased throughout the second half. Basketball game demands seem to induce significant metabolic-hormonal changes on players. Higher values of HR and glycemia were observed in the first half, but a more important increase of lipolytic variables was recorded in the second half. Changes in metabolic markers are role-dependent.